1995
DOI: 10.1017/s0950268800058155
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of invasiveHaemophilus influenzaeinfections in England and Wales in the pre-vaccination era (1990–2)

Abstract: SUMMARYThis survey defined the pattern of invasive Haemophilus influenzae infections during 1990-2 in six regions in England and Wales during the pre-vaccination era providing a baseline against which any changes in patterns of disease due to the introduction of the Haemophilus influenzae type b vaccination programme can be monitored. A total of 946 cases of invasive Haemophilus influenzae were recorded during the survey period of which almost 90 % were due to type b and most of the remainder were non-typeable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 13 publications
2
24
0
Order By: Relevance
“…In our study, 65% of all invasive H. influenzae infections in children aged !5 years occurred in infants !1 year of age, and the age distribution showed a peak for children aged 6-9 months. We found that 8.8% of the cases of invasive Hib disease were in hospitalized adults, a finding similar to the 12% [39] and 9% [40] reported in hospital studies from the United States and the United Kingdom. In contrast to data for blood cultures from a single hospital in Pakistan [18] but similar to data for CSF isolates from Bangladesh [21] and the United States [41], 97% of the H. influenzae isolates we recovered from CSF and blood specimens were Hib.…”
Section: Discussionsupporting
confidence: 87%
“…In our study, 65% of all invasive H. influenzae infections in children aged !5 years occurred in infants !1 year of age, and the age distribution showed a peak for children aged 6-9 months. We found that 8.8% of the cases of invasive Hib disease were in hospitalized adults, a finding similar to the 12% [39] and 9% [40] reported in hospital studies from the United States and the United Kingdom. In contrast to data for blood cultures from a single hospital in Pakistan [18] but similar to data for CSF isolates from Bangladesh [21] and the United States [41], 97% of the H. influenzae isolates we recovered from CSF and blood specimens were Hib.…”
Section: Discussionsupporting
confidence: 87%
“…Noncapsulated (nontypeable) H. influenzae is commonly carried in the pharynx, is one of the major causes of acute otitis media, and can cause diseases of the upper and lower respiratory tract, including sinusitis and pneumonia. These isolates may also cause invasive disease, and serious non-Hib disease in children is more commonly due to noncapsulated isolates than to encapsulated isolates of the non-Hib serotypes (1,2,10,17). In some countries where the Hib conjugate vaccines are used (e.g., the United Kingdom) there has been an increase in adult invasive disease due to non-Hib isolates, most of which is due to noncapsulated isolates (34).…”
mentioning
confidence: 99%
“…The capsule is a major determinant of the pathogenicity of H. influenzae. In the pre‐vaccination era, approximately 90% of the invasive cases were caused by type b strains (8, 9). Apart from the type b capsule, encapsulated strains can express five other structurally and antigenically distinct capsular polysaccharides (10).…”
mentioning
confidence: 99%